PENAMBAHAN SARI JERUK KALAMANSI (Citrus microcarpa, B.) DALAM PEMBUATAN SELAI PEPAYA - Sianipar, Yessica Hartita; Sumual, Maria Fransisca; Assa, Jan Rudolf (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2021)
ABSTRACTThe research was purposed to determine the addition of kalamansi orange juice and analyze the sensory and chemical characteristics of papaya jam. The research used a completely randomized trial design method with the treatment of adding kalamansi orange juice with concentrations of 0%, 5%, 10%, 15% and 20%. The sensory test of papaya jam with the observed parameters was organoleptic test of preference level with hedonic scale and scoring test for jam rub power. Followed by an analysis of the chemical properties of papaya jam, the level of acidity (pH), total acid, vitamin C and total sugar in papaya jam which got a high level of preference.The preferred level of papaya jam with the addition of kalamansi orange juice 0% to 20% had an average value in terms of color 3.72-4.08, in terms of taste 3.08-4.00, in terms of aroma 2.92-3, 48 and in terms of texture 2.92-3.80. To the power of papaya jam with the addition of orange juice from 0% to 20% had an average value of 2.96-4.32. In conclusion, the addition of 10% kalamsi orange juice had a preferred level of preference with a pH composition of 4.05, a total acid of 0.84%, vitamin C 27.43 mg / 100 g and a total sugar of 52.56%. Keywords: Jam, Papaya, Kalamansi. ABSTRAKPenelitian ini bertujuan untuk menentukan penambahan sari jeruk kalamansi dan menganalisis karakteristik sensoris dan kimia pada selai pepaya. Penelitian ini menggunakan metode percobaan rancangan acak lengkap dengan perlakuan penambahan sari jeruk kalamansi dengan konsentrasi 0%, 5%, 10%, 15% dan 20%. Pengujian sensoris selai pepaya dengan parameter yang diamati adalah uji organoleptik tingkat kesukaan dengan skala hedonik dan uji scoring untuk daya oles selai. Dilanjutkan dengan analisis sifat kimia selai pepaya yaitu, tingkat keasaman (pH), total asam, vitamin C dan total gula pada selai pepaya yang mendapatkan tingkat kesukaan tinggi. Tingkat kesukaan selai pepaya dengan penambahan sari jeruk kalamansi 0% sampai 20% memiliki nilai rata-rata dari segi warna 3,72-4,08, dari segi rasa 3,08-4,00, dari segi aroma 2,92-3,48 serta dari segi tekstur 2,92-3,80. Terhadap daya oles selai pepaya dengan penambahan sari jeruk kalamansi 0% sampai 20% memiliki nilai rata-rata 2,96-4,32. Pada kesimpulannya penambahan sari jeruk kalamansi 10% memiliki tingkat kesukaan yang disukai dengan komposisi pH 4,05, total asam 0,84%, vitamin C 27,43 mg/100 g dan total gula 52,56%. Kata kunci: Selai, Pepaya, Jeruk Kalamansi.